1991
DOI: 10.1172/jci115052
|View full text |Cite
|
Sign up to set email alerts
|

A single base substitution in the coding region for neurophysin II associated with familial central diabetes insipidus.

Abstract: To elucidate the molecular mechanism of familial central diabetes insipidus (FDI), we sequenced the arginine vasopressinneurophysin II (AVP-NPII) gene in 2 patients belonging to a pedigree that is consistent with an autosomal dominant mode of inheritance. 10 patients with idiopathic central diabetes insipidus (IDI) and 5 normals were also studied. The AVP-NPII gene, locating on chromosome 20, consists of three exons that encode putative signal peptide, AVP, NPII, and glycoprotein. Using polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(64 citation statements)
references
References 25 publications
3
61
0
Order By: Relevance
“…Some technical diffi culties in PCR amplifi cation and direct sequencing of AVP were encountered because this gene is extremely rich in G+C, especially in the last half of the gene where these nucleotides encompass more than 70% of the sequence, as already reported by other researchers (3).…”
Section: Familial Diabetes Insipidus Due To Avp Mutationmentioning
confidence: 81%
See 1 more Smart Citation
“…Some technical diffi culties in PCR amplifi cation and direct sequencing of AVP were encountered because this gene is extremely rich in G+C, especially in the last half of the gene where these nucleotides encompass more than 70% of the sequence, as already reported by other researchers (3).…”
Section: Familial Diabetes Insipidus Due To Avp Mutationmentioning
confidence: 81%
“…This familial disorder generally occurs some months to years after birth, and ongoing progressive AVP defi ciency has been described (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Since the mutation in this gene was first reported in 1991 by Ito et al [3], there have been 46 different mutations identified to date [2,[4][5][6][7][8]. Although the majority of mutations are located in the coding sequence of the signal peptide or the NPII domain [2], 18 different allelic variants are reported [2].…”
Section: Neurohypophyseal Diabetes Insipidus (Ndi) Is Caused By a Defmentioning
confidence: 99%
“…PCR conditions were: 1-min predenaturation at 96 C; 35 cycles of 1 min at 94 C, annealing for 1 min at 55-58 C, and extension for 1 min at 72 C; and 15-min elongation at 72 C. Buffer conditions have been described previously (18). Direct sequencing was performed in forward and reverse using dRhodamine (PE Applied Biosystems, Foster City, CA) or Thermo Sequenase II (Amersham Pharmacia Biotech Pharmacia, Piscataway, NJ) dye terminator sequencing kits and automated sequencers (Models 373A and 377; PE Applied Biosystems, Foster City, CA).…”
Section: Pcr and Direct Sequencing Of Dax1mentioning
confidence: 99%